Propuesta de un sistema de depuración del agua de bombeo utilizando el método de flotación con aire disuelto (daf) y floculantes para reducir los niveles de contaminación en la empresa pesquera hayduk s.a. - malabrigo. - Romero Chirinos, William Loanders (2014)
The main environmental problem facing companies fishmeal is pollution of marine waters due to the various effluents generated. Given this reality application of method arose with Flotation Dissolved Air and use of flocculants in the water treatment system pumping Pesquera Hayduk SA - Malabrigo in order to reduce pollution levels. The hypothesis states that if a significant reduction in pollution indicators occurs, then it will have reduced pollution levels. The economic evaluation of the DAF system reports an NPV of U.S. $ 520151 (calculated at a discount rate of 20% annually), monthly IRR of 67% and a payback period of 1.37 months. Environmental indicators point to significant achievements as a reduction of water consumption and energy source in the order of 25% and 20%, respectively. Likewise the recovery of solid fats and increases. For these technical reasons it is recommended to use this effluent treatment system and expand its use in other companies.